Barriers and facilitators to recognize and discuss depression and anxiety experienced by adults with vision impairment or blindness: a qualitative study - Edine P. J. van Munster; Hilde P. A. van der Aa; Peter Verstraten; Ruth M. A. van Nispen (BMC, 2021)
Abstract Background Depression and anxiety are highly prevalent, but often unrecognized in adults with vision impairment (VI) or blindness. The purpose of this study was to explore visually impaired and blind adults' views on facilitators and barriers in recognizing and discussing mental health problems. Methods Semi-structured interviews, based on the Integrated Model for Change, were conducted with 16 visually impaired or blind adults receiving support from three Dutch low vision service organizations. Interview data was analyzed using the framework approach. Results Participants perceived their focus on practical support with regard to their VI, lack of mental health literacy, and misattribution of symptoms of depression or anxiety as barriers for recognizing mental health problems. With regard to discussing mental health problems, they perceived difficulties in acknowledging their VI and mental health problems due to feelings of vulnerability and inequality. Participants mentioned that their social support system and healthcare providers (could) facilitate them in recognizing and discussing mental health problems. However, participants thought that healthcare providers currently often lacked the knowledge, skills and attitude to recognize and discuss this topic with their clients. Conclusion Our findings suggest that visually impaired and blind adults may experience several barriers to recognize, acknowledge and discuss mental health. Healthcare providers and social support systems seem essential for them in reducing these barriers. However, there might be a mismatch between the needs of visually impaired and blind adults and healthcare providers' knowledge, skills and attitude. Training healthcare providers may improve detection of depression and anxiety in adults with VI or blindness, and enhance clinician-patient communication on mental health.